A review of the taxonomic status of the New Caledonia Wattled Bat Chalinolobus neocaledonicus Revilliod, 1914 (Chiroptera: Vespertilionidae) and Chalinolobus gouldii venatoris Thomas, 1908 from northern Australia - Parnaby, Harry E; Divljan, Anja; Hoye, Glenn (Zootaxa, 2020)
The taxonomic status of the New Caledonia Wattled Bat Chalinolobus neocaledonicus Revilliod, 1914 has remained uncertain since its synonymy with mainland Australian Gould’s Wattled Bat C. gouldii (Gray, 1841) in 1971. Although Chalinolobus neocaledonicus is now widely accepted as a valid species, this was based on a tentative taxonomic opinion published in 1995. We examined most of the original material used to justify synonymy with C. gouldii, which included the type series of C. gouldii venatoris, a small northern Australian form that superficially resembles C. neocaledonicus but is currently not generally recognised as a valid subspecies. We found consistent differences in key diagnostic external and cranial criteria that support species status for C. neocaledonicus. We also review the taxonomic status of venatoris. Contrary to previous assessments, our re-interpretation of the taxonomic literature supports subspecific recognition of venatoris. Nevertheless, we are unable to conclusively resolve the status of venatoris because a more complex pattern of variation than a simple latitudinal size cline is apparent in C. gouldii. We argue that recognition of venatoris as the northern subspecies of C. gouldii has merit, pending a comprehensive analysis of variation in mainland C. gouldii to test for the presence of cryptic taxa.